THE EFFECTIVENESS OF PUBLIC HEALTH INTERVENTIONS IN REDUCING THE BURDEN OF INFECTIOUS DISEASES - Abdullah Hamed Mohammed Almatrafi, Mater Miqad F Alotaibi, Abdulaziz Mohammad yousef Alzeer,Dakheel Maashi Dalshammari, Abdullah Ali Abdulrahman Alhamoud, Saud Mohamed Saud Altamimi, Ziyad Alhumidi Almutairi, Fawaz Saud Alotaibi; Mohammed Najmi , Abdullah Mohammed Abdullah Aleisa , Yahya Ali Refaei , Samer Alhassan Hamdi , Muteb Mohammed Ghazi Alotaibi, Amro Ahmed khamjan, Abdu Ahmed Khamjan (Chelonian Research Foundation, 2022)
This study investigates the efficacy of several public health measures in mitigating the impact of infectious illnesses, including HIV/AIDS, viral hepatitis, sexually transmitted diseases (STDs), and tuberculosis (TB). The categorization system outlined in this document categorizes research in public health law and policy into many types, including studies on policymaking, mapping, implementation, intervention or assessment, and mechanisms. The study emphasizes the knowledge acquired from the analysis of research, studies on implementation, and evaluation research conducted in these fields. Mapping studies have shown deficiencies in laws and regulations, found legal provisions that do not adhere to optimal standards, and encouraged the spread of successful legal advancements. Implementation studies have evaluated the practicability, effectiveness, and possible negative outcomes of policy improvements, offering vital knowledge for state and municipal organizations. Assessment studies have used several approaches, such as retrospective evaluations and modeling tools, to analyze the effects of policy initiatives on the health of the community. The results provide direction for the development and implementation of health-promoting policies, assuring their feasibility, effectiveness, and avoidance of adverse outcomes. Keywords: Public health initiatives, infectious illnesses, policy research, mapping studies, implementation studies, evaluation studies.